Deep Proteome Mapping of Mouse Kidney Based on OFFGel Prefractionation Reveals Remarkable Protein Post- Translational Modifications - Magdeldin, Sameh (American Chemical Society, 2014)
[Image: see text] Performing a comprehensive nonbiased proteome analysis is an extraordinary challenge due to sample complexity and wide dynamic range, especially in eukaryotic tissues. Thus, prefractionation steps conducted prior to mass spectrometric analysis are critically important to reduce complex biological matrices and allow in-depth analysis. Here we demonstrated the use of OFFGel prefractionation to identify more low abundant and hydrophobic proteins than in a nonfractionated sample. Moreover, OFFGel prefractionation of a kidney protein sample was able to unveil protein functional relevance by detecting PTMs, especially when prefractionation was augmented with a targeted enrichment strategy such as TiO(2) phospho-enrichment. The OFFGel-TiO(2) combination used in this study was comparable to other global phosphoproteomics approaches (SCX-TiO(2), ERLIC-TiO(2), or HILIC-TiO(2)). The detailed mouse kidney proteome with the phosphopeptide enrichment presented here serves as a useful platform for a better understanding of how the renal protein modification machinery works and, ultimately, will contribute to our understanding of pathological processes as well as normal physiological renal functions.